Analysis of Internal Control Over Rice Supplies at Perum Bulog Padangsidimpuan City - Hasibuan, Masnilam; Harahap, Aswin Ramanda (Indonesian Journal of Advanced Research, 2024)
Inventory is a company's current assets which are quite material and are one of the important factors in supporting company activities. Therefore, good internal control must be carried out to secure inventory from theft, misappropriation and damage. The aim of this research is to determine the internal control carried out by Perum Bulog Padang Sidimpuan City in order to get a clear picture of whether the internal control of rice supplies implemented is effective. The method used in this research is a qualitative descriptive method used to describe the internal control of inventory at Perum Bulog Padang Sidimpuan City. From the research results, it was concluded that the internal control of rice supplies at Perum Bulog Padangsidimpuan City was quite effective, where there was a separation between functions related to the receipt and expenditure of rice. Monitoring of rice supplies is also carried out every day. However, Perum Bulog Padangsidimpuan City needs to improve weaknesses in its physical protection, namely by installing CCTV cameras in the warehouse to create more effective internal inventory monitoring.